Problems in the development of international academic mobility - Zhakyanova, A.M.; Kanagatov, M.K. (Journal of Oriental Studies, 2021)
In this article, the authors attempt to identify the problems of the development of academic mobility as a tool of soft power. Academic mobility through the prism of the concept of «Soft Power» acquires a new interpretation and provides an opportunity to improve the tools and mechanisms of interstate cooperation. The aim of this work is to identify the main problems in the development of academic mobility in the framework of international relations. In this regard, the tasks were set to study and characterize new challenges and opportunities in assessing trends both in the field of higher education and in the system of international relations. On the basis of statistical data, secondary data analysis, it is concluded that there is a need for a conceptual study of academic mobility in Kazakhstan; the existing grounds for the need to create a new image on the world stage that corresponds to Kazakhstan’s national interests and modern realities. Nowadays, the implementation of Kazakhstan’s “soft power” has many problems related to legal, financial, and economic aspects. Although the acting normative documents on the organization of students’ academic mobility in the Kazakhstani context have been motivated mainly by a sufficient empirical material that reflects the experience of practical activity of its implementation, there is a lack of fundamental work on the given research problem, which in its turn, aroused the interest of the authors of the article. Key words: academic mobility, soft power, internationalization of education, international relations.